Bessie Head : re-writing the romance : journalism, fiction (and gender) - Guldimann, Colette (Department of English Language and Literature, 2016)
This thesis examines the relationship between Bessie Head's work as a journalist during the late 1950s and two of her novels: the first written just after she had left formal journalism and the second a decade later. I claim, in this thesis, that early journalistic writing by Head, which has been critically ignored, and even dismissed, not only merits critical attention but, furthermore, that knowledge this work will yield new insights into Head's fictional writing for which she is famous. Between 1959 and 1960, before she left South Africa, Bessie Head wrote two weekly columns for children and teenagers, some book reviews and had a role in the production of "True Romance" stories for Home Post, a tabloid supplement to the Sunday newspaper Golden City Post. Head was involved in the production of these romances for over a year and I provide an analysis of the "True Romance" stories published in Home Post. I maintain that these romances, like all texts in popular romance genre (which I discuss) constructs the feminine in very particular ways. I locate this analysis within wider, but related, discussion about the representation of women in both Golden City Post and Drum magazine as they were both considered to be the authoritative newspapers representing black South African life in the 1950s. Head's columns, I claim, especially the one for teenagers, present constructions of the feminine, as well as the masculine, which are significantly at odds with the dominant representations of the feminine, and masculine, in the media I have mentioned, during the late 1950s. A close reading of the representations of gender which Head set up in this column, together with the book reviews she wrote, will give us new insight into her fictional work, particularly The Cardinals which is an early work written and set during this period but only published posthumously in 1993. Reading this novel against the background of the journalistic work and world Head was engaged in just before she wrote it will enable us to read its complexities, specifically those regarding gender and romance. I claim that Head also gave us what is probably the earliest gender perspective, and critique, of 1950s black journalism - a period generally considered to be a vibrant one for black journalism and writing in South Africa. In The Cardinals, which fictionally recreates the black journalistic milieu of the late 1950s in South Africa, Head suggests that black women journalists (and writers) found themselves facing a very different situation from black male journalists. Finally I suggest that with romance structure and the role which gender plays in the novel. Although critics have persistently read this novel as an idealistic, and unrealistic, romance with a happy ending, I suggest, in this thesis, that one can read the novel, in the light of Head's earlier work, as being a radical subversion of the romance.